Financial transaction rules of the disabled people through the legal maxim: "hardship begets facility" –an analytic jurisprudence study - Zakariyah, Habeebullah; Aminullahi, Sarafdeen (Zes Rokman Resources, 2018)
This article attempts to present new contributions and looks at modern perspectives, in addition to the previous studies on those disabled people in regard to their cases and its legal rulings, with provision of the appropriate rules for their behaviours and financial conditions in the current era, through a jurisprudential base "hardship begets facilitation". However, we commit ourselves in this research by employing indicative investigate and desk approach methodology, in order to highlight the sources of this legal maxim in the texts of Sharia and the effects. Meanwhile we address its effects on the financial transaction of the disabled people, through the opinions of the jurists and contemporary scholars on the whole issues. Finally, we mention the results and suggest some recommendations.